So sánh tốc độ tăng năng suất các nhân tố tổng hợp giữa các phương thức vận tải ở Việt Nam – Đo lường qua hàm sản xuất Cobb-Douglas - Nguyễn Hải , Quang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Total factor productivity plays a very important role in growth models. It represents in-depth and sustained growth. This study identifies and compares the total factor productivity growth among transport modes in Vietnam through the Cobb-Douglas production function. The results of data analysis over the period 2000–2017 show that capital, labor, and total factor productivity are factors affecting the output of the transport industry (ton-km of transport). However, their roles in the modes of transport are different. In recent years, modes of transport have grown mainly on capital increase in Vietnam. The total factor productivity growth in air transport is highest and has been increasing recently, while the other modes of transport do not. The results from this study are a basis to suggest implications for the comprehensive development of transport modes in Vietnam.
Keywords: Growth; TFP; Các phương thức vận tải; Hàm sản xuất